Hard Work and Hopefulness: A Mixed Methods Study of Music Students’ Status and Beliefs in Relation to Health, Wellbeing, and Success as They Enter Specialized Higher Education - Rose, Dawn C.; Sigrist, Carlo; Alessandri, Elena (Frontiers in Psychology, 2021)
Using mixed methods, we explored new music students’ concepts of wellbeing and success and their current state of wellbeing at a university music department in Switzerland. Music performance is a competitive and achievement-oriented career. Research suggests musicians face vocation-specific challenges to physical health and mental wellbeing but has yet to investigate music students’ beliefs about wellbeing and success. With a self-report questionnaire (n=99, new BA/MA students) we investigated new music students’ quality of life (WHO-5; WHOQoL-BREF) and self-efficacy (ASKU). Through qualitative workshops (17 groups, n=5-8) we explored students’ understanding of the term ‘wellbeing’, and how this relates to ‘success’. Over half new music students (55%) believed the institution has 40-60% responsibility for their wellbeing. A simple linear regression showed that self-efficacy could predict better wellbeing, explaining 12% of the variance. Self-efficacy predicts wellbeing for new music students (β1=8.81, p=.001). The 17 flipcharts generated 121 inputs clustered into themes. Four themes solely described ‘wellbeing’ (Health, Safety, Vitality, and Attitude) and four separately depict ‘success’ (Achieving Objectives, Recognition, Career, and Financial Goods). Some themes intersected as elements of both constructs (Intersection: Relationships & Environment, Development, Happiness, Meaningfulness, Balance and Authenticity). Four further themes illustrated the relationship between the two (Reciprocity, Conditionality, Stability and Perspectivity). Music students believe responsibility for wellbeing is shared between themselves and their institution. As they scored low on both self-efficacy and wellbeing, these findings are an urgent call for action for school management and stakeholders of the music student population